Răspuns :
Răspuns:
[tex]a) \frac{2 \times 6 + 5}{6} - \frac{11 \times 9 + 1}{9} \div \frac{4 \times 6 + 1}{6} = \\ = \frac{17}{6} - \frac{100}{9} \times \frac{6}{25} = \\ = \frac{17}{6} - \frac{8}{3} = \\ = \frac{17 - 16}{6} = \frac{1}{6} [/tex]
[tex]b) \frac{1 \times 25 + 2}{25} \div \frac{1 \times 49 + 5}{49} + \frac{1 \times 35 + 1}{35} \div \frac{2 \times 7 + 6}{7} = \\ = \frac{27}{25} \times \frac{49}{54} + \frac{36}{35} \times \frac{7}{20} = \\ = \frac{49}{50} + \frac{9}{25} = \\ = \frac{49}{50} + \frac{18}{50} = \frac{67}{50} [/tex]
[tex]c) \frac{49}{60} \times \frac{4}{1 \times 4 + 3} - \frac{3}{10} = \\ = \frac{49}{60} \times \frac{4}{7} - \frac{3}{10} = \\ = \frac{7}{15} - \frac{3}{10} = \\ = \frac{14 - 9}{30} = \frac{5}{30} = \frac{1}{6} [/tex]
Sper că te-am ajutat!
a) Introducem întregii în fracție și vom obține:
[tex]\it \dfrac{17}{6}-\dfrac{100}{9}\cdot\dfrac{6}{25}=\dfrac{1}{3}\Big(\dfrac{17}{2}-\dfrac{\ \ 600^{(25}}{3\cdot25}\Big)=\dfrac{1}{3}\Big(\dfrac{^{3)}17}{2}-\dfrac{^{2)}24}{3}\Big)=\\ \\ \\ =\dfrac{1}{3}\cdot \dfrac{51-48}{6}=\dfrac{1}{\not3}\cdot\dfrac{\not3}{6}=\dfrac{1}{6}[/tex]